Impact of dosing schedule on uptake of neuroprotective magnesium sulfate. (18th March 2020) - Cuff, Ryan D.; Sullivan, Scott A.; Chang, Eugene Y.
Abstract: Background: Preterm delivery <32-week gestation is associated with significant neurodevelopmental morbidity ranging from mild delay to profound disability. Several randomized trials have shown that magnesium sulfate (MgSO4 ) is an effective neuroprotectant, demonstrating reduced rates of cerebral palsy, death, and gross motor dysfunction for the neonate or infant. Dosing was not consistent among the major trials and the onus was placed on institutions by ACOG to develop and implement protocols with respect to MgSO4 as a neuroprotectant. A recent study demonstrated that MgSO4 exposure <12 h prior to delivery was associated with a decrease in CP compared to more remote exposure. Objective: To assess impact of dosing schedule on uptake of neuroprotective MgSO4 in patients delivering <32 weeks gestational age. Study design: A retrospective cohort study of all deliveries occurring <32 weeks' gestation at a single academic center between March–December 2014 and March–December 2015 was conducted. Institutional policy shifted in 2015 from MgSO4 bolus with continuous infusion based on the BEAM trial to a single bolus dose based on the PREMAG trial. Patients with preeclampsia, known fetal anomalies, and/or stillbirth were excluded from this analysis. Patients were identified through query of the Medical University of South Carolina Perinatal Information System (PINS) database with respect to whether or not they had received MgSO4 within 12 h of delivery. Chi-squared analysis was performed to compare the overall rate of MgSO4 exposure and MgSO4 exposure <12 h prior to delivery between groups. Fisher's exact test was used to evaluate maternal, obstetric, and neonatal variables among those receiving MgSO4 within 12 h of delivery in each cohort. Binary logistic regression analysis was performed to control for co-linear or potential confounding variables. Results: A total of 224 patients were identified, 115 delivered between March–December 2014 and 109 delivered between March–December 2015. With respect to MgSO4 exposure prior to delivery, 27 (23.5%) received MgSO4 in the 2014 cohort compared to 44 (40.4%) in the 2015 cohort (OR: 2.2, p < .01). Of those being exposed within 12 h of delivery, there were 16 (13.9%) maternal exposures in the 2014 cohort versus 28 (26.7%) in the 2015 cohort (OR: 2.15, p = .02). Of the 18 neonates delivered in 2014 there were four cases of grade III or IV intraventricular hemorrhage versus one case among the 36 neonates (2.7%) born in 2015 (0.04). This finding holds after controlling for race, preterm labor, gestational age, corticosteroid, birthweight, and indomethacin exposure. Conclusions: Dosing of neuroprotective MgSO4 according to PREMAG trial specifications was associated with a significantly greater percentage of patients having received neuroprotective magnesium at any point prior to delivery or within the 12 h prior to delivery when compared to dosing according to BEAM trial specifications.